2019
DOI: 10.4172/pharmaceutical-sciences.1000491
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antibacterial Activity of Cobalt(II) Complex of Curcumin

Abstract: Girish et al.: Antibacterial Activity of Curcumin-cobalt(II) Complex To improve the bioavailability of curcumin numerous approaches were attempted, which included complexation with metal ions. In the present study, a metal ion complex of cobalt(II) with curcumin was synthesized and screened for in vitro antibacterial activity in comparison with curcumin on seven bacterial strains, Bacillus subtilis, Escherichia coli, Klebsiella pneumoniae, Salmonella typhi, Shigella flexneri, Proteus vulgaris and Staphylococcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 22 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…In line with this, a good number of mononuclear (Girish et al, 2019; Pasdar et al, 2015) and binuclear (Gurumoorthy et al, 2014; Panda et al, 2015; Patel et al, 2009) mixed‐ligand complexes have been reported in the literature. In particular, Co(II) containing mixed ligand complexes appeared promising in solving diseases caused by Gram‐positive bacteria (Chang et al, 2010; Patel et al, 2009).…”
Section: Introductionmentioning
confidence: 70%
“…In line with this, a good number of mononuclear (Girish et al, 2019; Pasdar et al, 2015) and binuclear (Gurumoorthy et al, 2014; Panda et al, 2015; Patel et al, 2009) mixed‐ligand complexes have been reported in the literature. In particular, Co(II) containing mixed ligand complexes appeared promising in solving diseases caused by Gram‐positive bacteria (Chang et al, 2010; Patel et al, 2009).…”
Section: Introductionmentioning
confidence: 70%
“…Furthermore, the complex has a better safety profile than curcumin alone, as it is less likely to cause liver damage. [89][90][91] Also, many reports on the antimicrobial activity of cobalt (II) complexes with sulfanilamide derivatives have shown promising antimicrobial activity against a variety of Gram-positive/Gram-negative and fungi strains. [92][93][94][95][96][97] Irgi and his collaborators [98] indicated the potential antibacterial effect of cobalt (II) complexes with quinolone oxolinic acid, 2,2'-bipyridine, 2,2'-bipyridylamine, 1,10-phenanthroline, pyridine or 4-benzylpyridine ligands against Gramnegative (E. coli NCTC 29212 and Xanthomonas campestris ATCC 1395), and Gram-positive (S. aureus ATCC 6538 and B. subtilis ATCC 6633) bacterial strains.…”
Section: Biological Activitiesmentioning
confidence: 99%
“…[21,22,25] Besides the anticancer applications, metal-curcumin complexes are also reported to be antibacterial agents. [31][32][33][34] Curcumin can effectively suppress the growth of bacteria like Streptococcus, Staphylococcus, and Lactobacillus. [31,33] Ru II , Zn II complexes of curcumin have shown potential antimicrobial activities.…”
Section: Introductionmentioning
confidence: 99%
“…[31][32][33][34] Curcumin can effectively suppress the growth of bacteria like Streptococcus, Staphylococcus, and Lactobacillus. [31,33] Ru II , Zn II complexes of curcumin have shown potential antimicrobial activities. [33,34] Co is one of the bio-essential and highly biocompatible elements.…”
Section: Introductionmentioning
confidence: 99%